Arabica Beans Cafe / Mohd Hakimi Ismail ... [et al.] - Ismail, Mohd Hakimi; Yulam Mustafa, Mohd Hasnol Hisham; Ahmad Fawzi, Muhamad Faisal; Sayid Mohamad, Syed Fadzly; Masmeera, Musa
Arabica Beans Cafe is a business that serves especially Sungai Petani Town people 'Arabica Beans', a different and finest coffee beans from arround the world such as Columbia, Brazil, Costa Rica and New Guinea. The Arabica Beans is expected to operate in January 2003. It concept is to create a range of distinctive, individually styled coffees by combining traditional craft skills with modern technology and equipment. 'The enterprise will quickly established a growing demand from customer who were no longer content with pre-pack commercial blends, but were in search of fresher, more flovorful alternatives. The success of Arabica Beans will grew with its reputation of providing an outstanding range of fine coffees presented in stylish and high quality packaging.